Lagerstroemia densa (Lythraceae), a new species from Daqing Mountain, Guangxi Zhuang Autonomic Region, China - Gu, Cuihua; Ma, Dan Dan; Zhu, Xu Dan; Tembrock, Luke R.; Wang, Xian (Phytotaxa, 2015)
The new species Lagerstroemia densa from Daqing Mountain, Chongzuo City, Guangxi Zhuang Autonomic Region (China) is described and illustrated. The morphological characteristics of the new species and two morphologically similar species are compared. The new species resembles L. subcostata in leaf shape but differs mainly in petal color, floral tube morphology and indumentum, and the shape of the capsule, and is similar to L. excelsa in the shape of the floral tube lobes and inflorescences, from which it differs by its glabrous, acute leaves, racemiform inflorescences, and glabrous calyx lobes.